2015
DOI: 10.1259/bjr.20150545
|View full text |Cite
|
Sign up to set email alerts
|

Visually stratified CT honeycombing as a survival predictor in combined pulmonary fibrosis and emphysema

Abstract: Visual estimation of honeycombing extent on CT can help in the prediction of prognosis in CPFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The presence of honeycombing has been previously reported as predictive of worse outcome in interstitial lung disease [13][14][15]. Those with 'possible' or 'inconsistent' UIP CT pattern with minimal honeycombing have also been reported to have improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of honeycombing has been previously reported as predictive of worse outcome in interstitial lung disease [13][14][15]. Those with 'possible' or 'inconsistent' UIP CT pattern with minimal honeycombing have also been reported to have improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…In cluster 2, the degree of honeycombing, reticulation, and emphysema was not significantly different from cluster 3, whereas the extent of GGO was higher. In many studies, honeycombing and reticulation are defined as a CT fibrosis score, and prognosis is worse with an increasing extent of honeycombing and reticulation [4, 10, 20]. Our study found that the extent of GGO in patients with severe fibrosis may affect prognosis.…”
Section: Discussionmentioning
confidence: 55%
“…Disease extent on CT has been used as a prognostic determinant of IPF. Visually stratifying the extent of honeycombing on CT may help predict prognosis in IPF with emphysema [20]. However, visual scoring of IPF by radiologists shows high interobserver variability and is somewhat subjective.…”
Section: Discussionmentioning
confidence: 99%
“…9 Kim et al also showed that low DL CO (HR: 0.97, P = 0.017) was independently associated with increased mortality in CPFE patients with honeycombing on CT (HR: 1.95, P = 0.018), but FVC was not. 23 In a study by Kishaba et al, FEV 1 /FVC > 1.2 was a prognostic factor for mortality (HR: 1.93, P = 0.005) in CPFE with finger clubbing (HR: 2.26, P = 0.015). 24 Our study showed that, in IPF-only patients, FVC decline was a significant predictor of mortality, as were FVC and DL CO .…”
Section: Discussionmentioning
confidence: 94%